Tattoo free setup for partial breast irradiation: A feasibility study. Issue 4 (4th April 2019) - Jimenez, Rachel B.; Batin, Estelle; Giantsoudi, Drosoula; Hazeltine, William; Bertolino, Kendell; Ho, Alice Y.; MacDonald, Shannon M.; Taghian, Alphonse G.; Gierga, David P.
Abstract: Purpose: Patients undergoing external beam accelerated partial breast irradiation (APBI) receive permanent tattoos to aid with daily setup alignment and verification. With the advent of three‐dimensional (3D) body surface imaging and two‐dimensional (2D) x‐ray imaging‐based matching to surgical clips, tattoos may not be necessary to ensure setup accuracy. We compared the accuracy of conventional tattoo‐based setups to a patient setup without tattoos. Materials/methods: Twenty consecutive patients receiving APBI at our institution from July 10, 2017 to February 13, 2018 were identified. All patients received tattoos per standard of care. Ten patients underwent setup using tattoos for initial positioning followed by surface imaging and 2D matching of surgical clips. The other ten patients underwent positioning using surface imaging followed by 2D matching without reference to tattoos. Overall setup time and orthogonal x‐ray‐based shifts after surface imaging per fraction were recorded. Shift data were used to calculate systematic and random error. Results: Among ten patients in the "no tattoo" group, the average setup time per fraction was 6.83 min vs 8.03 min in the tattoo cohort ( P < 0.01). Mean 3D vector shifts for patients in the "no tattoo" group were 4.6 vs 5.9 mm in the "tattoo" cohort ( P = NS). Mean systematic errors in the "no tattoo" group were: 1.2 mm (1.5 mm SD) superior/inferior, 0.5 mm (1.6 mm SD) right/left, and 2.3 mm (1.9 mm SD) anterior/posterior directions. Mean systematic errors in the "tattoo" group were: 0.8 mm (2.2 mm SD) superior/inferior, 0.3 mm (2.5 mm SD) right/left, and 1.4 mm (4.4 mm SD) anterior/posterior directions. The random errors in the "no tattoo" group ranged from 0.6 to 0.7 mm vs 1.2 to 1.7 mm in the "tattoo" group. Conclusions: Using both surface imaging and 2D matching to surgical clips provides excellent accuracy in APBI patient alignment and setup verification with reduced setup time relative to the tattoo cohort. Skin‐based tattoos may no longer be warranted for patients receiving external beam APBI.